Biomechanics of head injury in olympic taekwondo and boxing - Fife, G.; Pieter, W. (Biology of Sport, 2013)
Objective: The purpose was to examine differences between taekwondo kicks and boxing punches in resultant linear head acceleration (RLA), head injury criterion (HIC15), peak head velocity, and peak foot and fist velocities. Data from two existing publications on boxing punches and taekwondo kicks were compared. Methods: For taekwondo head impacts a Hybrid II Crash Dummy (Hybrid II) head was instrumented with a tri-axial accelerometer mounted inside the Hybrid II head. The Hybrid II was fixed to a height-adjustable frame and fitted with a protective taekwondo helmet. For boxing testing, a Hybrid III Crash Dummy head was instrumented with an array of tri-axial accelerometers mounted at the head centre of gravity. Results: Differences in RLA between the roundhouse kick (130.11±51.67 g) and hook punch (71.23±32.19 g, d=1.39) and in HIC15 (clench axe kick: 162.63±104.10; uppercut: 24.10±12.54, d=2.29) were observed. Conclusions: Taekwondo kicks demonstrated significantly larger magnitudes than boxing punches for both RLA and HIC.